Система локалізації радіоактивного пилу в підпокрівельному просторі об’єкта "Укриття" - Павлюченко, М.І. (Проблеми безпеки атомних електростанцій і Чорнобиля, 2017)
Система локалізації радіоактивного пилу в об’єкті «Укриття» виконує функцію утримання радіоактивних речовин в установлених межах. Функція включає локалізацію радіоактивного пилу шляхом нанесення захисного полімерного покриття на забруднені поверхні, осадження пилу з повітря підпокрівельного простору за допомогою зрошення простору розчином, який осаджує пил. Система локализации радиоактивной пыли в объекте "Укрытие" выполняет функцию удержания радиоактивных веществ в установленных пределах. Функция включает локализацию радиоактивной пыли, путем нанесения защитного полимерного покрытия на загрязненные поверхности, осаждение пыли из воздуха подкровельного пространства с помощью орошения пространства раствором, который осаждает пыль. The system localize of radioactive dust in an object "Ukryttya" performs the duty of withholding of radionuclidess in the set limits. A function includes localization of radio-active dust, by causing of the polymeric sheeting on muddy surfaces, settling dust from air of subroofing space by means of irrigation of space solution which settles dust. Systems and methods for controlling the protective properties of the polymer coating in the object "Ukryttya". After the relevant reconstruction the updated dust-suppressing installation (UDSI) could be used at the phase of new safe confinement putting into operation. During full/partial dismantlement of unstable constructions the UDSI would be also dismantled, its functions being transferred to the mobile dust-suppressing installation.